The Diagnostic Value of Urinary Secretory Antigen Target of 6 kDa in Childhood Pulmonary Tuberculosis - Iskandar, Agustin; Lawanto, Ella Melissa; Zulhaidah, Maimun; Olivianto, Ery; Handono, Kusworini; Anshory, Muhammad; Aprilia, Andrea; Aryati, Aryati (Open Access Macedonian Journal of Medical Sciences, 2021)
Introduction. Childhood tuberculosis (TB) is difficult to diagnosed and is based together on clinical and microbiology examinations. Since in children signs and symptoms of TB are not typical and sputum is difficult to be obtained, Mycobacterium tuberculosis (Mtb) antigen detection could be considered as a non invasive method for early detection of childhood TB. ESAT-6 is a low molecular weight specific protein that plays an important role in Mtb virulence. Aim. To determine the diagnostic value of urinary ESAT-6 for the diagnosis of childhood tuberculosis. Methodology.This was a cross-sectional study, with consecutive sampling collection . in children aging between 0-14 years suspected for pulmonary TB based on the clinical presence of :cough lasting more than 2 weeks, fever without clear ethiology, loss of body weight or poor weight gain, fatigue, malaise with positive history of contact with sputum smear from adult TB patients. Diagnosis of pulmonary TB was based on clinical presentation plus tuberculin positive skin test, chest x-ray, AFB staining and/or sputum culture. Subjects who met the inclusion criteria but unconfirmed by clinical and microbiological were considered as control (non-TB group). Urinary ESAT-6 level was analyzed by using ELISA. Cut off value and AUC was determined using ROC Statistical Analysis (SPSS 20.0). Sensitivity and specificity was measured from 2x2 crosstable. Result. Between the 61 studied children with suspected TB, 46/61 (75%) were finally diagnosed with TB, with 34/46 (74%) microbiologically confirmed cases either by sputum microscopy 31/34 (91%) or culture 3/34 (9%), whereas 15/61 (25%) subjects were not-confirmed cases (non-TB group). The mean value of urinary ESAT-6 level was higher in TB than non-TB group, Mean (SD) [4.855(6.714)] ng/mLvs [1.503(0.946)] ng/mL; p=<0.001(Mann-Whitney test). At ROC curve analysis ,the cut off value of urinary ESAT-6 in subjects TB confirmed both with clinical plus microbiology evaluation as reference standard was 1,91 ng/mL, with sensitivity 72% and specificity 67%. While the cut off value of ESAT-6 in TB subjects confirmed group only by clinical signs was 2.45 ng/mL, with sensitivity 65% and specificity 67%. Conclusion. For TB Diagnosis in Children, Urinary ESAT-6 urine could be considered of value when utilized in addition to microbiological tests and clinical examination.